Regenerated building material

By setting up a filling groove in the recycled building materials and filling the reinforced polymer feed, a honeycomb structure is formed, which solves the problem of insufficient compressive strength of the existing materials, and achieves higher compressive strength and improved material performance.

CN119877772APending Publication Date: 2025-04-25GUANGZHOU YAOFANG INTELLIGENT ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933168.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The compressive strength of existing recycled building materials is insufficient, making it difficult to meet a wider engineering demand.

Method used

By providing a filling groove in the regenerated building material and filling the reinforced polymer feed into the filling groove, a honeycomb structure is formed to enhance the bearing capacity and rigidity of the material.

Benefits of technology

On the basis of material saving, the compressive strength of recycled building materials is improved, breathability and thermal insulation properties are improved, making them more suitable for a wide range of engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877772A_ABST
    Figure CN119877772A_ABST
Patent Text Reader

Abstract

The invention discloses a regenerated building material, and relates to the technical field of building material preparation. The regenerated building material comprises a lower base layer, a lower pouring layer, a connecting layer, an upper pouring layer and an upper base layer from bottom to top, a pouring groove is formed in the connecting layer, a reinforced polymer supplementary material is poured into the pouring groove, multiple groups of pore openings are preset between the pouring groove and a hollow outer frame layer, and every two of the multiple groups of pore openings are connected to form a honeycomb structure. A honeycomb structure formed by a plurality of groups of pores is preset between the pouring groove and the hollow outer frame layer, so that a regenerated building material dispersedly bears external force from all directions, resistance to extrusion force is formed, the bearing capacity can be further improved on the basis of saving materials, the pores are uniformly distributed, and the service life of the regenerated building material is prolonged. And in addition, the pouring groove is filled with the reinforced polymer supplementary material, the interior of the regenerated building material is filled, the bearing capacity and rigidity are enhanced, and the structure of the regenerated building material is more compact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material preparation, in particular to a recycled building material. Background Art

[0002] Recycled building materials are materials that are recycled, reused or sustainably developed and reused in the construction industry. They help reduce the demand for virgin resources, lower the environmental impact of construction and promote sustainable construction.

[0003] The use of recycled building materials can also reduce the carbon emissions of buildings, improve the quality of indoor environment, and increase the sustainability of buildings. However, recycled building materials also face some challenges, such as the quality and performance may not be as good as virgin materials, and may require additional costs.

[0004] Based on this, many related technical processes have been developed for using construction waste as recycled aggregate to prepare recycled building materials. Actual engineering applications have also proved that recycled building materials are well compatible with other materials, but the rigidity and compressive resistance of the prepared recycled building materials need to be further improved. Their strength varies and is difficult to unify. At the same time, they can only meet the needs of some projects with lower strength requirements. Therefore, it is necessary to further improve the compressive strength of recycled building materials so that they can be suitable for a wider range of engineering needs. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a recycled building material to solve the problems raised in the above background technology.

[0006] To achieve the above purpose, the present invention is implemented by the following technical scheme: a recycled building material, which includes a lower base layer, a lower pouring layer, a connecting layer, an upper pouring layer and an upper base layer from bottom to top, a pouring groove is arranged in the connecting layer, and the space size of the pouring groove is 65% to 70% of the size of the recycled building material, and the enhanced polymer filler is poured into the pouring groove. There are multiple groups of pore openings preset between the pouring groove and the hollow outer frame layer, and the multiple groups of pore openings are connected in pairs to form a honeycomb structure, wherein the formation of the honeycomb structure can disperse the external forces from all sides, so that the honeycomb structure can form a resistance to the extrusion force, and the bearing capacity can be further improved on the basis of saving materials. Furthermore, in the recycled building material, the pore openings are evenly distributed, which improves the air permeability and thermal insulation performance of the material. Furthermore, the interior of the pouring groove is filled with enhanced polymer filler, and the interior of the recycled building material is filled to enhance the bearing capacity and rigidity, making its structure more compact.

[0007] A further improvement of the technical solution of the present invention is that the reinforced polymer supplement material is selected to be a mixture of alumina powder and stainless steel fibers.

[0008] A further improvement of the technical solution of the present invention is that in order to ensure the wear resistance of the prepared recycled building materials and provide a construction foundation for subsequent construction, the lower base and upper base serve as the outermost layers of the recycled building materials, and the surfaces of the lower base and upper base are both granular.

[0009] A further improvement of the technical solution of the present invention is that the recycled building material includes the following components in parts by weight: 60-80 parts of cement, 30-45 parts of recycled building aggregate, 15-24 parts of high-sulfur petroleum coke slag, 5-12 parts of fly ash, 3-6 parts of activator, 6-9 parts of enhanced polymer supplement, 1-4 parts of flame retardant, and 2-5 parts of compatibilizer.

[0010] A further improvement of the technical solution of the present invention is that the fly ash contains at least SiO2, Al2O3, Fe2O3, CaO, MgO and SiO3, wherein the minimum component content in one component of fly ash is SiO2≥49.41%, Al2O3≥25.47%, Fe2O3≥3.54%, CaO≥4.21%, MgO≥1.59%, and SiO3≥0.83%.

[0011] A further improvement of the technical solution of the present invention is that the flame retardant is selected as any one of aluminum hydroxide, magnesium hydroxide, red phosphorus or antimony oxide, and the compatibilizer is selected as any one of maleic anhydride grafted polyethylene, EPDM, and POE.

[0012] A further improvement of the technical solution of the present invention is that the preparation of the recycled building material comprises the following specific steps:

[0013] S1: After removing the metal, wood and plastic materials in the building recycled aggregate, select an appropriate amount of cement and building recycled aggregate for mixing, stirring and crushing. The particle size after crushing is controlled to be 3mm-6mm, and the usable cement and building recycled aggregate mixed particles are screened out through a double screen drum;

[0014] S2: After mixing and stirring high-sulfur petroleum coke slag and fly ash, the mixture is crushed by a pulverizer, and the particle size after crushing is controlled to be 1600um-1650um. The available high-sulfur petroleum coke slag and fly ash mixed particles are screened out by a double-screen drum.

[0015] A further improvement of the technical solution of the present invention is that the preparation of the recycled building material further comprises:

[0016] S3: Weigh the crushed and sieved cement, building recycled aggregate mixed particles and high-sulfur petroleum coke slag, fly ash mixed particles, add water, activator, flame retardant and compatibilizer to mix evenly, put the mixed raw materials into the outer frame mold to form a hollow outer frame layer, wherein a pouring groove is formed in the hollow outer frame layer, and the raw materials and part of the enhanced polymer supplement are poured into the pouring groove. A plurality of groups of pores are dug at the pouring place between the pouring groove and the hollow outer frame layer, and the plurality of groups of pores are connected into a honeycomb structure to finally form a lower mold, and the upper mold is made in the same way. The upper and lower molds are pressed and formed at a pressure of 15MPa. After forming, the surface layers of the upper and lower molds are ground into particles by a roller structure, and are placed away from light for 24 hours. The raw material embryo is sent to an autoclave and steamed at a steam pressure of 18MPa for 6-8 hours.

[0017] A further improvement of the technical solution of the present invention is that the ambient temperature in the autoclave is controlled to be 70-80° C. during steam curing for 6-8 hours at a steam pressure of 18 MPa.

[0018] Compared with the prior art, the invention has the beneficial effect that, by presetting a honeycomb structure formed by a plurality of groups of pores between the pouring groove and the hollow outer frame layer, the recycled building materials are dispersed to bear the external forces from all sides, thus forming resistance to the extrusion force, and the bearing capacity can be further improved on the basis of saving materials. The pores are evenly distributed, which improves the air permeability and heat insulation performance of the material. In addition, the interior of the pouring groove is filled with enhanced polymer supplementary material to fill the interior of the recycled building material, thereby enhancing the bearing capacity and rigidity, and making the structure more compact.

[0019] In terms of materials, fly ash and high-sulfur petroleum coke slag containing rich SiO2, Al2O3, Fe2O3, CaO, MgO and SiO3 are selected to assist in the preparation of recycled building materials. They have excellent performance and a strength grade of MU25, turning waste raw materials into effective recycled building resources, creating more economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the overall structure of recycled building materials;

[0021] Figure 2 A cross-sectional view of the structure of the connecting layer in the recycled building material;

[0022] Figure 3 Flowchart specifically prepared for recycled building materials.

[0023] In the figure, 1, lower base layer; 2, lower perfusion layer; 3, connection layer; 4, upper perfusion layer; 5, upper base layer; 6, perfusion trough; 7, enhanced polymer supplement; 8, pore opening. DETAILED DESCRIPTION

[0024] Various exemplary embodiments, features and aspects of the present application will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0025] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0026] In addition, in order to better illustrate the present application, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, and elements well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application.

[0027] The invention provides a recycled building material, which comprises, from bottom to top, a lower base layer, a lower pouring layer, a connecting layer, an upper pouring layer and an upper base layer, wherein a pouring groove is arranged in the connecting layer, and the space size of the pouring groove is 65% to 70% of the size of the recycled building material, and an enhanced polymer supplement is poured into the pouring groove, and a plurality of groups of pore openings are preset between the pouring groove and the hollow outer frame layer, and the plurality of groups of pore openings are connected in pairs to form a honeycomb structure.

[0028] The honeycomb structure can disperse the external forces from all sides, so that the honeycomb structure can resist the extrusion force, and can further improve the bearing capacity on the basis of saving materials. Furthermore, in the recycled building materials, the pores are evenly distributed, which improves the air permeability and heat insulation performance of the materials.

[0029] Furthermore, the interior of the pouring tank is filled with reinforced polymer filler, which fills the interior of the recycled building material to enhance the bearing capacity and rigidity, making its structure more compact.

[0030] The reinforced polymer filler material is a mixture of alumina powder and stainless steel fibers.

[0031] In order to ensure the wear resistance of the prepared recycled building materials and provide a construction foundation for subsequent construction, the lower base and the upper base serve as the outermost layers of the recycled building materials, and the surfaces of the lower base and the upper base are both granular.

[0032] Embodiment 1:

[0033] The recycled building material includes the following components in parts by weight: 70 parts of cement, 35 parts of recycled building aggregate, 16 parts of high-sulfur petroleum coke slag, 8 parts of fly ash, 4 parts of activator, 8 parts of enhanced polymer supplement, 2 parts of flame retardant and 3 parts of compatibilizer.

[0034] Fly ash contains at least SiO2, Al2O3, Fe2O3, CaO, MgO and SiO3, among which the minimum component content in one component of fly ash is SiO2≥49.41%, Al2O3≥25.47%, Fe2O3≥3.54%, CaO≥4.21%, MgO≥1.59% and SiO3≥0.83%.

[0035] The flame retardant is aluminum hydroxide, and the compatibilizer is maleic anhydride grafted polyethylene.

[0036] The preparation of recycled building materials includes the following specific steps:

[0037] S1: After removing the metal, wood and plastic materials in the building recycled aggregate, select an appropriate amount of cement and building recycled aggregate for mixing, stirring and crushing. The particle size after crushing is controlled to be 4mm, and the usable cement and building recycled aggregate mixed particles are screened out through a double screen drum;

[0038] S2: After mixing and stirring high-sulfur petroleum coke slag and fly ash, the mixture is crushed by a pulverizer, and the particle size after crushing is controlled to be 1600um-1650um. The available high-sulfur petroleum coke slag and fly ash mixed particles are screened out by a double-screen drum.

[0039] S3: Weigh the crushed and sieved cement, building recycled aggregate mixed particles and high-sulfur petroleum coke slag, fly ash mixed particles, add water, activator, flame retardant and compatibilizer to mix evenly, put the mixed raw materials into the outer frame mold to form a hollow outer frame layer, wherein a pouring groove is formed in the hollow outer frame layer, and the raw materials and part of the enhanced polymer supplementary material are poured into the pouring groove, and multiple groups of pores are dug at the pouring place between the pouring groove and the hollow outer frame layer. The multiple groups of pores are connected into a honeycomb structure to finally form a lower mold, and the upper mold is made in the same way. The upper and lower molds are fitted and pressed into shape at a pressure of 15MPa. After forming, the surface layers of the upper and lower molds are ground into particles using a roller structure, and are placed away from light for 24 hours. The raw material embryos are sent to an autoclave and steamed at a steam pressure of 18MPa for 7 hours.

[0040] The ambient temperature in the autoclave was controlled at 70-80°C during curing for 7 hours using a steam pressure of 18 MPa.

[0041] The above-mentioned middle and outer frame molds are selected from brick molds that are easy to test. All indicators are carried out in accordance with the provisions of "Test Methods for Wall Bricks" and "Non-fired Bricks Fly Ash Bricks". The test results are as follows:

[0042] Average compressive strength: 26.18 MPa; flexural strength: 41.3 MPa; bulk density: 153 kg / m 3 ; Water absorption rate 17.15%; Post-freezing compressive strength - 20.13MPa.

[0043] Embodiment 2:

[0044] The recycled building material includes the following components in parts by weight: 70 parts of cement, 35 parts of recycled building aggregate, 18 parts of high-sulfur petroleum coke slag, 8 parts of fly ash, 4 parts of activator, 8 parts of enhanced polymer supplement, 2 parts of flame retardant and 3 parts of compatibilizer.

[0045] Fly ash contains at least SiO2, Al2O3, Fe2O3, CaO, MgO and SiO3, among which the minimum component content in one component of fly ash is SiO2≥49.41%, Al2O3≥25.47%, Fe2O3≥3.54%, CaO≥4.21%, MgO≥1.59% and SiO3≥0.83%.

[0046] The flame retardant is aluminum hydroxide, and the compatibilizer is maleic anhydride grafted polyethylene.

[0047] The preparation of recycled building materials includes the following specific steps:

[0048] S1: After removing the metal, wood and plastic materials in the building recycled aggregate, select an appropriate amount of cement and building recycled aggregate for mixing, stirring and crushing. The particle size after crushing is controlled to be 4mm, and the usable cement and building recycled aggregate mixed particles are screened out through a double screen drum;

[0049] S2: After mixing and stirring high-sulfur petroleum coke slag and fly ash, the mixture is crushed by a pulverizer, and the particle size after crushing is controlled to be 1600um-1650um. The available high-sulfur petroleum coke slag and fly ash mixed particles are screened out by a double-screen drum.

[0050] S3: Weigh the crushed and sieved cement, building recycled aggregate mixed particles and high-sulfur petroleum coke slag, fly ash mixed particles, add water, activator, flame retardant and compatibilizer to mix evenly, put the mixed raw materials into the outer frame mold to form a hollow outer frame layer, wherein a pouring groove is formed in the hollow outer frame layer, and the raw materials and part of the enhanced polymer supplementary material are poured into the pouring groove, and multiple groups of pores are dug at the pouring place between the pouring groove and the hollow outer frame layer. The multiple groups of pores are connected into a honeycomb structure to finally form a lower mold, and the upper mold is made in the same way. The upper and lower molds are fitted and pressed into shape at a pressure of 15MPa. After forming, the surface layers of the upper and lower molds are ground into particles using a roller structure, and are placed away from light for 24 hours. The raw material embryos are sent to an autoclave and steamed at a steam pressure of 18MPa for 7 hours.

[0051] The ambient temperature in the autoclave was controlled at 70-80°C during curing for 7 hours using a steam pressure of 18 MPa.

[0052] The above-mentioned middle and outer frame molds are selected from brick molds that are easy to test. All indicators are carried out in accordance with the provisions of "Test Methods for Wall Bricks" and "Non-fired Bricks Fly Ash Bricks". The test results are as follows:

[0053] Average compressive strength: 26.78MPa; flexural strength: 41.9MPa; bulk density: 152kg / m 3 ; Water absorption rate 17.87%; Post-freezing compressive strength - 21.74MPa.

[0054] From the comparison between Example 1 and Example 2, it can be seen that when other conditions are kept the same, the increase in the total amount of high-sulfur petroleum coke slag does not significantly increase the compressive and flexural strengths of the building materials. It can be seen that it is feasible to manufacture building materials using high-sulfur petroleum coke slag in combination with enhanced polymer supplementary materials and pores of a honeycomb structure, and the MU25 standard can be reached.

[0055] Embodiment three:

[0056] The recycled building material comprises the following components in parts by weight: 70 parts of cement, 35 parts of recycled building aggregate, 18 parts of high-sulfur petroleum coke slag, 8 parts of fly ash, 4 parts of activator, 2 parts of flame retardant and 3 parts of compatibilizer.

[0057] Fly ash contains at least SiO2, Al2O3, Fe2O3, CaO, MgO and SiO3, among which the minimum component content in one component of fly ash is SiO2≥49.41%, Al2O3≥25.47%, Fe2O3≥3.54%, CaO≥4.21%, MgO≥1.59% and SiO3≥0.83%.

[0058] The flame retardant is aluminum hydroxide, and the compatibilizer is maleic anhydride grafted polyethylene.

[0059] The preparation of recycled building materials includes the following specific steps:

[0060] S1: After removing the metal, wood and plastic materials in the building recycled aggregate, select an appropriate amount of cement and building recycled aggregate for mixing, stirring and crushing. The particle size after crushing is controlled to be 4mm, and the usable cement and building recycled aggregate mixed particles are screened out through a double screen drum;

[0061] S2: After mixing and stirring high-sulfur petroleum coke slag and fly ash, the mixture is crushed by a pulverizer, and the particle size after crushing is controlled to be 1600um-1650um. The available high-sulfur petroleum coke slag and fly ash mixed particles are screened out by a double-screen drum.

[0062] S3: Weigh the crushed and sieved cement, building recycled aggregate mixed particles, high-sulfur petroleum coke slag, and fly ash mixed particles, add water, activator, flame retardant, and compatibilizer, and mix evenly. Load the evenly mixed raw materials into the outer frame mold to form a hollow outer frame layer, and finally form a lower mold. The upper mold is made in the same way. The upper and lower molds are pressed into shape at a pressure of 15MPa. After forming, the surface layer of the upper and lower molds is milled into particles using a roller structure. The particles are placed away from light for 24 hours, and the raw material embryos are sent to the autoclave and steamed at a steam pressure of 18MPa for 7 hours.

[0063] The ambient temperature in the autoclave was controlled at 70-80°C during curing for 7 hours using a steam pressure of 18 MPa.

[0064] The above-mentioned middle and outer frame molds are selected from brick molds that are easy to test. All indicators are carried out in accordance with the provisions of "Test Methods for Wall Bricks" and "Non-fired Bricks Fly Ash Bricks". The test results are as follows:

[0065] Average compressive strength: 19.12MPa; flexural strength: 38.75MPa; bulk density: 151.3kg / m 3 ; Water absorption rate 18.78%; Post-freezing compressive strength - 17.47MPa.

[0066] By comparing Example 1 and Example 3 with Example 2 and Example 3, it can be seen that the reinforced polymer supplement poured into the pouring tank in combination with multiple groups of pores can enhance the bearing capacity and rigidity of the material, and by choosing to burn waste fly ash and high-sulfur petroleum coke slag, the waste raw materials are turned into effective renewable construction resources, creating more economic and environmental benefits.

[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A recycled building material, characterized in that: The recycled building material includes, from bottom to top, a lower base layer, a lower pouring layer, a connecting layer, an upper pouring layer and an upper base layer. A pouring groove is arranged in the connecting layer. The spatial size of the pouring groove is 65% to 70% of the size of the recycled building material. Reinforced polymer supplementary material is poured into the pouring groove. A plurality of groups of pore openings are preset between the pouring groove and the hollow outer frame layer. The plurality of groups of pore openings are connected in pairs to form a honeycomb structure.

2. A recycled building material according to claim 1, characterized in that: The reinforced polymer supplement material is selected to be a mixture of alumina powder and stainless steel fiber.

3. A recycled building material according to claim 1, characterized in that: The lower base layer and the upper base layer serve as the outermost layers of the recycled building material, and the surfaces of the lower base layer and the upper base layer are both granular.

4. The recycled building material according to claim 1, characterized in that: The recycled building material comprises the following components in parts by weight: 60-80 parts of cement, 30-45 parts of recycled building aggregate, 15-24 parts of high-sulfur petroleum coke slag, 5-12 parts of fly ash, 3-6 parts of activator, 6-9 parts of enhanced polymer supplement, 1-4 parts of flame retardant and 2-5 parts of compatibilizer.

5. A recycled building material according to claim 4, characterized in that: The fly ash contains at least SiO2, Al2O3, Fe2O3, CaO, MgO and SiO3, wherein the minimum component content in one component of fly ash is SiO2≥49.41%, Al2O3≥25.47%, Fe2O3≥3.54%, CaO≥4.21%, MgO≥1.59%, SiO3≥0.83%.

6. A recycled building material according to claim 5, characterized in that: The flame retardant is selected from any one of aluminum hydroxide, magnesium hydroxide, red phosphorus or antimony oxide, and the compatibilizer is selected from any one of maleic anhydride grafted polyethylene, EPDM and POE.

7. A recycled building material according to claim 6, characterized in that: The preparation of the recycled building material comprises the following specific steps: S1: After removing the metal, wood and plastic materials in the building recycled aggregate, select an appropriate amount of cement and building recycled aggregate for mixing, stirring and crushing. The particle size after crushing is controlled to be 3mm-6mm, and the usable cement and building recycled aggregate mixed particles are screened out through a double screen drum; S2: After mixing and stirring high-sulfur petroleum coke slag and fly ash, the mixture is crushed by a pulverizer, and the particle size after crushing is controlled to be 1600um-1650um. The available high-sulfur petroleum coke slag and fly ash mixed particles are screened out by a double-screen drum.

8. The recycled building material according to claim 4, characterized in that: The preparation of the recycled building material also includes: S3: Weigh the crushed and sieved cement, building recycled aggregate mixed particles and high-sulfur petroleum coke slag, fly ash mixed particles, add water, activator, flame retardant and compatibilizer to mix evenly, put the mixed raw materials into the outer frame mold to form a hollow outer frame layer, wherein a pouring groove is formed in the hollow outer frame layer, and the raw materials and part of the enhanced polymer supplement are poured into the pouring groove. A plurality of groups of pores are dug at the pouring place between the pouring groove and the hollow outer frame layer, and the plurality of groups of pores are connected into a honeycomb structure to finally form a lower mold, and the upper mold is made in the same way. The upper and lower molds are pressed and formed at a pressure of 15MPa. After forming, the surface layers of the upper and lower molds are ground into particles by a roller structure, and are placed away from light for 24 hours. The raw material embryo is sent to an autoclave and steamed at a steam pressure of 18MPa for 6-8 hours.

9. The recycled building material according to claim 8, characterized in that: The ambient temperature in the autoclave is controlled at 70-80°C during curing at a steam pressure of 18 MPa for 6-8 hours.